A parallel equivalence algorithm based on MPI for GNSS data processing. Issue 3 (2nd September 2021) - Jiang, Chunhua; Xu, Tianhe; Du, Yujun; Sun, Zhangzhen; Xu, Guochang
ABSTRACT: A modified algorithm combining equivalence theory with MPI technology to improve Global Navigation Satellite System data processing efficiency is presented. The reservation of covariance matrix, elimination of unknowns and parallelism of the equivalence algorithm are derived. Experimental results show that the algorithm can improve the efficiency of processing 100 IGS stations by 56% with negligible precision loss. Moreover, the proposed approach has higher efficiency than the leastsquares and Gauss-Jordan parallel method and this advantage is more obvious as computational scale increases. Further experiments on a clustershow the more nodes used, the higher the efficiency it can achieve.